New System for the Classification of Epiphyseal Separation of the Coracoid Process: Evaluation of Nine Cases and Review of the Literature - Takamitsu Mondori; Yoshiyuki Nakagawa; Shimpei Kurata; Shuhei Fujii; Takuya Egawa; Kazuya Inoue; Yasuhito Tanaka (Advances in Orthopedics)
Objectives and Design. Epiphyseal separation of the coracoid process (CP) rarely occurs in adolescents. In this retrospective case series, we reviewed the data of nine patients treated at our center and those of 28 patients reported in the literature. This injury can be classified into three types according to the injured area: Type I, base including the area above the glenoid; Type II, center including the coracoclavicular ligament (CCL); and Type III, tip with the short head of the biceps and coracobrachialis, as well as the pectoralis minor. Patients/Participants. A total of 37 patients were included in the analysis. Data on sex, age, cause and mechanism of injury, separation type, concomitant injury around the shoulder girdle, treatment, and functional outcomes were obtained. Main Outcome Measurements and Results. Type I is the most common type. The cause of injury and associated injury around the shoulder girdle were significantly different between Type I, II, and III fractures. The associated acromioclavicular (AC) dislocation and treatment were significantly different between Type I and III fractures. Our new classification system reflects the clinical features, imaging findings, and surgical management of epiphyseal separation of the CP. Type I and II fractures are mostly associated with AC dislocation and have an associated injury around the shoulder girdle. Type III fractures are typically caused by forceful resisted flexion of the arm and elbow. Although the latter are best managed surgically, whether conservative or surgical management is optimal for Type I and II fractures remains controversial. Conclusions. We noted some differences in the clinical characteristics depending on the location of injury; therefore, we aimed to examine these differences to develop a new system for classifying epiphyseal separation of the CP. This would increase the clinicians’ awareness regarding this injury and lead to the development of an appropriate treatment.